Supplement to the Charity Organisation Review - The Charity Organisation Review
1915-07 1915 1910s 4 pages 4 CHARITY ORGANISATION REVIEW Provincial Society. The Committee of the Nottingham Charity Organisation Society require the services of a trained and experienced lady secretary. Salary up to £125, according to qualifications and experience. Applications, with copies of recent testimonials, to be sent to J. Briggs, Esq. (Chairman), Darby House, Southey Street, Nottingham. Library of the Council. The following Publications have been received for the Library during the past month:— Soziale Praxis und Archiv fur Volkswohlfahrt. Berlin. June 3, 10, 17, 1915 Volkswohl. Organ des Zentralvereins für das Wohl der Arbeitenden Klassen. May 20, 27; June 3, 10, 17, 1915. The Survey. New York C.O.S. May 29; June 5, 12, 1915. Board of Trade Labour Gazette. June 1915. The Economic Journal. June 1915. La Revue Philanthropique. Paris. June 1915. The American Economic Review. June 1915. Report of the Board of Education, 1913-1914, presented by the Right Hon Lord Sanderson, G.C B HOSPITAL LETTERS have been received from:— Mrs. Lane, Edward Bond. Esq., Mrs R Saunderson, Lady Susan Gilmour, St. George's, Hanover Square. Committee, Miss Stevenson. 463/box 99